Stunting and development of behavior - Verawati Simamora; Sabar Santoso; Nanik Setiyawati (Intelektual Pustaka Media Utama, 2019)
The current study aimed to examine the relationship between the incidence of Stunting, characteristics of mother with the development of toddlers 24-59 months in the work area of Sentolo I Public Health Center, KulonProgo Regency. The study design used was a retrospective cohort (historical cohort). The research was conducted in May 2019. The population of this study was all under-fives under the Sentolo Health Center I work area. There were 130 respondents consisting of 65 exposed groups and 65 unexposed groups participated in this study. The analysis used in this study used Chi-square.Developments wasdetected using Denver II. The results of the bivariate analysis showed that there was a relationship betweenStunting and the development of toddlers 24-59 months (p=0.003). There was no relationship between sex and number of siblings with the development of children under five (p=0.808). There is a significant relationship between the level of knowledge of mothers and toddler development (p=0.859). There is a relationship between the level of education of mothers with development (p=0.003). There is a relationship between family income and the development of (p=0.001), but there is no relationship between the work of mothers and children under five years (p=0.001).There is a relationship between Stunting and developing toddlers 24-59 months in the working area of Sentolo I Public Health Center, KulonProgo Regency.